Would Multilateral Trade Reform Benefit Sub-Saharan Africans? - Anderson, Kym (World Bank, Washington, DC, 2012)
This paper examines whether the Sub-Saharan African economies could gain from multilateral trade reform in the presence of trade preferences. The World Bank's LINKAGE model of the global economy is employed to examine the impact first of current trade barriers and agricultural subsidies, and then of possible outcomes from the WTO's Doha round. The results suggest moving to free global merchandise trade would boost real incomes in Sub-Saharan Africa proportionately more than in other developing countries or in high-income countries, despite a terms of trade loss in parts of the region. Farm employment and output, the real value of agricultural and food exports, the real returns to farm land and unskilled labor, and real net farm incomes would all rise in the region, thereby alleviating poverty. A Doha partial liberalization of both agricultural and nonagricultural trade could significantly benefit the region.